2005
DOI: 10.1128/aac.49.2.650-655.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Cefpirome in Subcutaneous Adipose Tissue of Septic Patients

Abstract: The objective of the present study was to evaluate whether cefpirome, a member of the latest class of broadspectrum cephalosporins, sufficiently penetrates subcutaneous adipose tissue in septic patients. After the administration of the drug at 2 g, tissue cefpirome concentrations in septic patients (n ‫؍‬ 11) and healthy controls (n ‫؍‬ 7) were determined over a period of 4 h by means of microdialysis. To assess the antibacterial effect of cefpirome at the target site, the measured pharmacokinetic profiles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 30 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…The results showed that FCZ recovery is concentration independent and inversely proportional to the flow rate, in agreement with previously reported data (20). Independent of the method employed, whether dialysis or retrodialysis, the FCZ recovery rate was around 50% in vitro as well as in vivo.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results showed that FCZ recovery is concentration independent and inversely proportional to the flow rate, in agreement with previously reported data (20). Independent of the method employed, whether dialysis or retrodialysis, the FCZ recovery rate was around 50% in vitro as well as in vivo.…”
Section: Resultssupporting
confidence: 81%
“…infections (20), this study was conducted to investigate, by microdialysis, FCZ penetration into the kidneys of healthy and Candida albicans-infected Wistar rats and to establish the relationship between total plasma and free renal levels of the drug.…”
mentioning
confidence: 99%
“…The degree of tissue penetration with ceftobiprole correlates well with other cephalosporins such as cefpodoxime (14), cefixime (14), cefpirome (10,21), and cefaclor (7) ( Table 2). There was a significant difference between the fAUC of plasma and the AUC of both tissues and between the AUC of muscle and the AUC of s.c. adipose tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Also, free drug concentrations at the site of action/infection are much more relevant in determining efficacy (15,24), and exploring the concentration at the site of action has been recommended by regulatory agencies (1,2,8). One technique that has proven useful for the measurement of free-drug concentrations in subcutaneous (s.c.) adipose tissue and skeletal muscle is microdialysis (6,7,10,14,16,21).…”
mentioning
confidence: 99%
“…The colonies are then counted and backextrapolated to the original volume to determine colony forming units per milliliter. For a more realistic simulation of in vivo PK, changing antibiotic concentrations in culture tubes for dynamic pharmacokinetic/ pharmacodynamic studies may be applied (74,75). This can either be provided by continuous adjustment or by means of a dynamic circulation model.…”
Section: Mhbmentioning
confidence: 99%